(untitled) (Journal of Informatics Education and Research, 2025)
This narrative review explores the potential of Restorative Justice (RJ) principles as a framework for ethical redress in the financial sector, addressing prevalent consumer grievances stemming from financial fraud, mis-selling, and broader consumer harm.[1] Traditional redress mechanisms, such as litigation and arbitration, often fall short in comprehensively addressing the multifaceted harm experienced by victims, focusing predominantly on punitive or compensatory outcomes rather than holistic restoration of relationships and trust.[2] Employing an Antecedents, Decisions, Outcomes (ADO) framework, this paper synthesizes existing literature on RJ, ethical finance, and consumer protection to analyze how RJ can complement or potentially transform current dispute resolution practices. The review identifies key antecedents of financial harm, examines decision-making processes in ethical responses and stakeholder engagement, and assesses the outcomes of trust-building, victim satisfaction, and reintegration within a financial context. Empirical evidence from various fields, including criminal justice, demonstrates RJ’s effectiveness in achieving higher victim satisfaction, improved restitution rates, and enhanced accountability, suggesting a promising pathway for application in finance.[3] Challenges related to regulatory frameworks, industry adoption, and the unique complexities of financial misconduct are discussed, alongside opportunities for proactive ethical remediation and technology integration. This paper contributes to the burgeoning discourse on ethical finance by proposing a victim-centered, relationship-repairing approach to redress, offering practical implications for financial institutions, regulators, and policymakers seeking to foster a more trustworthy and resilient financial ecosystem.[4]